Controlled green synthesis of hybrid organo-inorganic nanomaterials based on poly(ethylene terephthalate) and silver nanoparticles by X-ray radiolysis - O. V. Arzhakova; A. A. Dolgova; A. Yu. Yarysheva; A. A. Zezin (eXPRESS Polymer Letters)
Self-confined synthesis of silver nanoparticles (AgNPs) within mesoporous host matrixes based on poly(ethylene terephthalate) (PET) upon X-ray radiolysis is studied. Mesostructured PET matrixes with a porosity of 35 vol% and pore dimensions below 10 nm were prepared and loaded with Ag+ ions via the mechanism of environmental crazing. Upon subsequent X-ray irradiation of silver-loaded samples, Ag+ ions experience reduction into Ag0 within mesopores. In this case, solvated electrons, alcohol radicals, and acetaldehyde act as effective reducing agents. The calculations show that the X-ray absorption dose rate for the solutions of silver nitrate (33.6 Gy/s) is nearly three times higher than that of pure PET (10.1 Gy/s). This contrast allows a selective synthesis of AgNPs within mesopores whereas the dose rate for the PET matrix lies within the level of sterilization. Mesoporous matrixes provide confined conditions for the synthesis of AgNPs with mean dimensions of ~2–3 nm and also serve as a stabilizing medium that prevents their aggregation and spares the use of any capping agents. This reagent-free approach offers a new route for preparing diverse hybrid organo-inorganic nanomaterials with desired functional properties.